Navigating the ‘Infodemic’: How People in Six Countries Access and Rate News and Information about Coronavirus - Nielsen, R; Fletcher, R; Newman, N; Brennen, J; Howard, P (Reuters Institute for the Study of Journalism, 2020)
In this report, we use survey data collected in late March and early April 2020 to document and understand how people in six countries (Argentina, Germany, South Korea, Spain, the UK, and the US) accessed news and information about COVID-19 in the early stages of the global pandemic, how they rate the trustworthiness of the different sources and platforms they rely on, how much misinformation they say they encounter, and their knowledge of and responses to the coronavirus crisis.